Aquaponic gardening : a step-by-step guide to raising vegetables and fish together - Bernstein, Sylvia (New Society Publishers, 2011)
Aquaponics is a revolutionary system for growing plants by fertilising them with the waste water from fish in a sustainable closed system. This definitive do-it-yourself home manual gives you various tools you need to create your own aquaponic system and enjoy healthy, safe, fresh and delicious food